An acoustic backscattering technique for the detection of transient cavitation produced by microsecond pulses of ultrasound - Roy, R; Madanshetty, S; Apfel, R (Acoustical Society of America, 1990)
An acoustic backscattering technique for detecting transient cavitation produced by 10‐μs‐long pulses of 757‐kHz ultrasound is described. The system employs 10‐μs‐long, 30‐MHz center frequency tone bursts that scatter from cavitation microbubbles. Experiments were performed with suspensions of hydrophobic polystyrene spheres in ultraclean water. Transient cavitation threshold pressures measured with the active cavitation detector (ACD) were always less than or equal to those measured using a passive acoustic detection scheme. The measured cavitation thresholds decreased with increasing dissolved gas content and increasing suspended particle concentration. Results also show that ultrasonic irradiation of the polystyrene sphere suspensions by the ACD lowered the threshold pressure measured with the passive detector. A possible mechanism through which suspensions of hydrophobic particles might nucleate bubbles is presented.